Bangalore-sur-Seine? (Economist, 2013)
The article looks at the 2013 founding of a higher education program in software development in France called 42, noting it is a private institution being created by telecommunications entrepreneur Xavier Niel and is designed to provide educational opportunities for low-income residents.